DESAIN ARSITEKTUR DATA WAREHOUSE PADA DATA TRANSAKSI PENJUALAN ROTTE BAKERY - Devi Julisca Sari; Siska Kurnia Gusti; Alwis Nazir; Elin Haerani; Fadhilah Syafria (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
The increasingly fierce competition between competitors requires companies to be able to compete and maintain their existence in order to continue to grow, for that utilizing information technology such as data warehouses will play a large enough role, because optimal data processing will produce quality information in supporting companies to take appropriate policies. as well as increasing the productivity and effectiveness of the company's performance. The application of the data warehouse can be started by making an architectural design that will be made, for that the researcher aims to provide recommendations for the design of the data warehouse architecture on the sales transaction data of Rotte Bakery by applying the Nine Steps Kimball method. The final result of this research is the application of the Nine Steps Kimball method and the integration of transaction data through the ETL process (extract, transform, load) successfully produces data stored in the data warehouse only the data that is needed and has been uninformed, so that data processing only takes a long time. shorter time in supporting appropriate policy making and achieving business strategies in order to be able to keep pace with the business competition